Feasibility of Swamp Paddy Farming with New Superior Varieties and Different Planting System - Alfayanti Alfayanti; Wilda Mikasari; Taupik Rahman (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2020)
Alfayanti A, Wilda M, Taupik R. 2020. Feasibility of swamp paddy farming with new superior varieties and different planting system. Jurnal Lahan Suboptimal: Journal of Suboptimal Lands 9(1): 50-56.Efforts to fulfil the community food demands could be achieved by swamp land optimization. One technology that can be developed on swamp land is utilization of new superior variety and planting system. Economic feasibility is one of considerations forÂ  farmers to adopt a technology innovation. The study aimed to determine the combination of the most economically viable new superior variety and planting system to be developed in swamp rice farming. The study was conducted from May-August 2016 in Karang Anyar Village Semidang Alas Maras district, Seluma Regency. There are 7 New Superior VarietiesÂ  of swamp paddy cultivated; Inpara 1, 2, 3, 6, 7, 8, and Dendang and 1 existing variety as benchmark variety, Cigeulis. The planting system applied were legowo planting system (2:1) with insertion and without insertion. The data used to achieve the research objectives is primary data in the form of farming data to calculate economic benefits and feasibility. Farm profit is calculated using partial analysis whereas economic feasibility is calculated by evaluating the break even point and R/C ratio. The results showed that Inpara 6 with legowo planting system with insertion yield the largest profit Rp 15.096.600,-/ha with R/C ratio of 2.92.